Regional Differences in Case Mix and Peri-operative Outcome After Elective Abdominal Aortic Aneurysm Repair in the Vascunet Database. Issue 6 (June 2015) - Mani, K.; Venermo, M.; Beiles, B.; Menyhei, G.; Altreuther, M.; Loftus, I.; Björck, M.
Abstract : Objective/background: National differences exist in the outcome of elective abdominal aortic aneurysm (AAA) repair. The role of case mix variation was assessed based on an international vascular registry collaboration. Methods: All elective AAA repairs with aneurysm size data in the Vascunet database in the period 2005–09 were included. AAA size and peri-operative outcome (crude and age adjusted mortality) were analysed overall and in risk cohorts, as well as per country. Glasgow Aneurysm Score (GAS) was calculated as risk score, and patients were stratified in three equal sized risk cohorts based on GAS. Predictors of peri-operative mortality were analysed with multiple regression. Missing data were handled with multiple imputation. Results: Patients from Australia, Finland, Hungary, Norway, Sweden and the UK ( n = 5, 895) were analysed; mean age was 72.7 years and 54% had endovascular repair (EVAR). There were significant variations in GAS (lowest = Finland [75.7], highest = UK [79.4], p for comparison of all regions < .001), proportion of AAA < 5.5 cm (lowest = UK [6.4%], highest = Hungary [29.0%]; p < .001), proportion undergoing EVAR (lowest = Finland [10.1%], highest = Australia [58.9%]; p < .001), crude mortality (lowest = Norway [2.0%], highest = Finland [5.0%]; p = .006), and age adjusted mortality (lowest = Norway [2.5%], highest = Finland [6.0%]; p = .048). Both aneurysm size and peri-operative mortality were highest among patients with a GAS >82. Of those with a GAS >82, 8.4% of men and 20.8% of women had an AAA <5.5 cm. Conclusion: Important regional differences exist in case selection for elective AAA repair, including variations in AAA size and patient risk profile. These differences partly explain the variations in peri-operative mortality. Further audit is warranted to assess the underlying reasons for the regional variation in case-mix.